Pengembangan Sistem Pengadaan dan Monitoring Aset Pada Kantor Desa Bajarum Berbasis Web Menggunakan Metode PIECES - Dody Erlangga; Minarni Minarni (LPPM Universitas Bhinneka Nusantara, 2022)
The Village Law stipulates that the Village has the power and origin of adequate funds to be able to control the potential it controls to promote the economy and welfare of its people. Through the efficient, effective and transparent procurement of goods and services by the Village Government, it is very helpful to realize the welfare of the village community as is the case with Kantor Desa Bajarum. Kantor Desa Bajarum has followed the Ministry of Home Affairs guidelines on the procurement of village goods and services in the operational process of procuring goods and services. However, in its implementation, the performance of kasi kesra is still very slow because the process of procuring goods and services to monitoring village assets is still in the form of manual input without automation. The data verification process is also carried out by checking one by one so that it is less efficient. In addition, manual data input makes it vulnerable to cases or fraud in the form of corruption of village assets by changing, modifying data so that the facts of the documentation or reports are different from the facts in the field. By utilizing the PIECES (Performance, Information, Economic, Control, Efficiency, Services) method, these problems can be overcome by developing an Information System for procurement and monitoring of village assets. System development is carried out using the Waterfall method. System Design utilizes UML (Unified Modeling Language). This web-based system is built with the PHP programming language and MySQL database. System testing method using Blackbox. This system has been able to run and is optimally implemented at the Kantor Desa Bajarum.